Prevalence and antimicrobial susceptibility pattern of Stenotrophomonas maltophilia isolated from peritoneal fluid cultures of dialysis patients - Krishnan, Shinu; Murali, Anusha; Babu, Asalatha Ratheesh; Gopal, Anila (International Journal of Research in Medical Sciences, 2026)
Background: Stenotrophomonas maltophilia (S. maltophilia) is an important cause of nosocomial infections, particularly in immunocompromised patients, such as patients with indwelling catheters. Blood stream infections are a leading cause of morbidity among patients undergoing dialysis. Prevalence and Antimicrobial Susceptibility pattern of Stenotrophomonas maltophilia isolated from peritoneal fluid cultures of Dialysis Patients. Methods: This single-center, retrospective, case–control study was conducted between April 2025 and January 2026. Patients who were undergoing dialysis at a tertiary care hospital, south Kerala and were diagnosed with S. maltophilia were included in this study. The demographic data, clinical characteristics and initial treatment data of the patients were analyzed to determine the risk factors for peritoneal dialysis- related S. maltophilia peritonitis. Results: A total of 370 peritonitis cases were recorded during the study period. Seven patients with S. maltophilia peritonitis and 21 controls (three controls to one case) were included in this study. The incidence of S. maltophilia peritonitis was significantly more frequent among patients with diabetes mellitus compared with controls (80.0% vs. 20.0%, p=0.004) and among patients with higher white blood cell counts in the dialysate after appropriate antibiotic therapy 2561/µl (349–4654/µl) vs. 20/µl (20–23/µ), p<0.001) than among the control patients. Although all the patients were treated with appropriate antibiotics following the identification of S. maltophilia, they had a significantly higher rate of catheter removal than the controls (80.0% vs. 0.0%, p=0.0003). Conclusions: Diabetes mellitus may be an important risk factor for S. maltophilia peritonitis in patients undergoing peritoneal dialysis.